How reliable is the mass variation in the Siberian permafrost region as observed by GRACE mission? - Shabanloui, Akbar; Müller, Jürgen (2015)
Permafrost generally and in Siberia (Russia) especially plays a key role for global hydrological mass transport, climate change and the eco-system of the Earth. In this study, surface and sub-surface mass variations in the Siberian permafrost region based on the gravitational approach (i.e. from GRACE mission) are estimated, and investigated to what extent the mass transport estimates are reliable and realistic. On the other hand, hydrological mass variations in this region are determined based on the geometrical approach using satellite (radar/laser) altimetry re-tracking data (e.g. Jason-2, ICESat) and satellite imagery (e.g. LandSat). In addition, hydrological surface mass variations are extracted from global hydrological water cycle models based on various in-situ hydrological observations, e.g. precipitation, evapotranspiration and run-off data. In this study, we quantify and asses the signal errors and its contributions to the integral mass variations in Siberia including error bars and determine to what extent GRACE results can provide mass variations which are caused by permafrost changes.